Emphysematous gastritis after metastatic malignant melanoma: a radiological surprise - Ng, Chiak Yot; Firdaus Hayati; Chandran Nadarajan (BMJ Publishing Group, 2020)
Malignant melanoma is cancer of the skin which commonly metastasises to the stomach. There have been no reported cases of emphysematous gastritis secondary to metastasis of malignant melanomas, to date. However, a 61-year-old woman with metastatic malignant melanoma of the left great toe presented to us with symptoms of severe left hypochondrium pain associated with high-grade fever, gross abdominal distension and recurrent vomiting. Two months earlier, metastasis was observed to have spread to the stomach and inguinal lymph nodes. At this stage, the patient opted for traditional medication instead of definitive surgery and chemotherapy. Radiological imaging revealed an emphysematous change to the stomach which was radiologically consistent with gastric malignant melanoma. Unfortunately, the patient succumbed to this rare condition.